Psychological Dynamics of Patients with Schizophrenia Psychological Disorders Psychological Dynamics Of Schizophrenia Psychological Disorders Patients - Onggo, Mega Indrawati; Dianovinina, Ktut; Dimas, Samuel (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2019)
The number of people with schizophrenia is increasing every year. Schizophrenia is also a severe psychological disorder. The purpose of the study is to know the dynamics of schizophrenia disorders by knowing the causal factors internally and externally and the interaction of the two factors. The research uses case study methods with a qualitative approach. The number of research participants is one person, namely Ryan, diagnosed with schizophrenia in 2010. Examination using interviews, observations, and several psychological test tools. The results show that some of the factors that influence the emergence of schizophrenia disorders. (1) Internal factors such as personality type, maladaptive coping skills, consumption drugs - especially those containing amphetamine. (2) External factors in the form of parenting patterns and problems encountered. These internal and external factors interact with each other making a person vulnerable to schizophrenia and triggering a relapse. The results of the study can help prevent future schizophrenia disorders through parental psychoeducation and interventions on coping skills and emotional regulation of schizophrenia disorders.